Erosion Control Treatment Using Geocell and Wheat Straw for Slope Protection. (12th April 2021) - Song, Xiaoruan; Huang, Miansong; He, Shiqin; Song, Gaofeng; Shen, Ruozhu; Huang, Pengzhi; Zhang, Guanfang
Abstract : Slope failure triggered by soil erosion under rainfall remains one of the most difficult problems in geotechnical engineering. Slope protection with planting vegetation can be used to reinforce the soil and stabilize the slope, but the early collapse of the planting soil before the complete growth of plants becomes a major issue for this method. This paper has proposed a composite soil treatment and slope protection method using the geocell structures and the wheat straw reinforcement. The geocell structures improve the stability of the planting soil and provide a stable and fixed environment for the vegetation, while the wheat straw reinforces the soil and also increases the fertility. The authors have performed a total of 9 experiments in this work that are classified into three groups, i.e., the unsupported slopes, the geocell reinforced, and the geocell and wheat straw composite reinforced with a consideration of three different rainfall intensities. The progressive slope failure development during the rainfall was assessed, as well as the soil erosion, the slope displacement, and the water content. The results show that the slope failure increases as the rainfall continues, and the soil degradation increases with the intensity of rainfall. The soil treatment using geocell improves the slope stability, but the geocell and wheat straw composite reinforcement has the best erosion control and slope protection.